Iterative conjugate heat transfer analysis for heat transfer enhancement of an externally cooled three‐phase induction motor. Issue 1 (1st January 2017) - Tiwari, Ankit; Yavuzkurt, Savas
Abstract : A novel iterative conjugate heat transfer method is proposed for thermal modelling of a drill pump motor which is a constant speed three‐phase induction motor. The major advantage of this technique is that it enables computational fluid dynamics (CFD) and heat transfer analysis of the rotor and the stator in a segregated manner. The two are then coupled in a separate annulus model, which represents the air gap, via boundary conditions on the annulus walls. This greatly reduces the total number of computational cells and enables good quality mesh generation – a pre‐requisite for accurate CFD predictions. To validate this method, a baseline CFD and heat transfer analysis was done using FLUENT and the maximum temperature prediction was found to be within 1.75% of the previously done experiments on the existing design of the machine. Further, this method was applied to develop a heat transfer enhancement solution which reduced the maximum temperature in the drill motor from 203.5 °C to 172.9 °C.